Rancang Bangun Sistem Administrasi Tata Usaha Barang Milik Negara Di Lembaga Layanan Pendidikan Tinggi Wilayah Iii Jakarta Berbasis Website - Sari, Yunita; Iqratama, Farhan (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2025)
Current information technology shows rapid growth and requires devices such as computers orapplications to manage data and information to ensure efficient data processing. Informationsystems are crucial in operating institutional activities such as operational control, strategicplanning, and performing other managerial functions (Zulkarnain et al., 2020). The HigherEducation Service Institution Region III is a government agency in Jakarta aimed at improvinghigher education standards under the Ministry of Education, Culture, Research, and Technology.The State-Owned Goods Administration is a department or work group within the HigherEducation Service Institution Region III Jakarta that is fully responsible for all operationalactivities within the Higher Education Service Institution Region III. Operational activities in theState-Owned Goods Administration of the Higher Education Service Institution Region IIIJakarta are still carried out manually without an application system to record all operationalactivities. Currently, the State-Owned Goods Administration of the Higher Education ServiceInstitution Region III is striving for digitalization through the SATU project, which involvesdesigning an application to support operational activities. However, the current design has notyet fully met the operational needs of the State-Owned Goods Administration, thus requiring refinement in the form of the design and development of the State-Owned Goods AdministrationSystem for the Higher Education Service Institution Region III Jakarta